2013
DOI: 10.2147/ijn.s43417
|View full text |Cite
|
Sign up to set email alerts
|

Nano-hole induction by nanodiamond and nanoplatinum liquid, DPV576, reverses multidrug resistance in human myeloid leukemia (HL60/AR)

Abstract: Abstract:Recently nanoparticles have been extensively studied and have proven to be a promising candidate for cancer treatment and diagnosis. In the current study, we examined the chemo-sensitizing activity of a mixture of nanodiamond (ND) and nanoplatinum (NP) solution known as DPV576, against multidrug-resistant (MDR) human myeloid leukemia (HL60/AR) and MDR-sensitive cells (HL60). Cancer cells were cultured with different concentrations of daunorubicin (DNR) (1 × 10 −9 -1 × 10 −6 M) in the presence of selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 49 publications
0
13
0
Order By: Relevance
“…17,38,5154 Similarly, some in vitro and in vivo studies have employed a nanodiamond and nanoplatinum mixture to demonstrate nanodiamond- and nanoplatinum-mediated dendritic cell activation, T cell proliferation, chemosensitization of a multidrug resistant human myeloid leukemia cell line and structural alteration of breast cancer cells. 43,55–57 However, the in vivo use of this mixture was through coating of the mixture onto cloths lining the mice cages and not through systemic administration. Additionally, FNDs have been used in a number of imaging experiments related to cancer research, ranging from immunofluorescence studies in a number of cell lines to sentinel lymph node mapping in small animals.…”
Section: Discussionmentioning
confidence: 99%
“…17,38,5154 Similarly, some in vitro and in vivo studies have employed a nanodiamond and nanoplatinum mixture to demonstrate nanodiamond- and nanoplatinum-mediated dendritic cell activation, T cell proliferation, chemosensitization of a multidrug resistant human myeloid leukemia cell line and structural alteration of breast cancer cells. 43,55–57 However, the in vivo use of this mixture was through coating of the mixture onto cloths lining the mice cages and not through systemic administration. Additionally, FNDs have been used in a number of imaging experiments related to cancer research, ranging from immunofluorescence studies in a number of cell lines to sentinel lymph node mapping in small animals.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, a solution of ND and NP increased the percentages of T-lymphocytes CD4 + and CD8 + of aged mice, which may be useful for preventing immune dysfunction [21]. Previous studies that have investigated the effects of DPV576 on cancer cells have shown that this solution of ND and NP is an effective tool for fighting cancer cells [2224]. Although the toxicity of nanomaterial is dose- and time-dependent [25], we are not aware of any published studies that have shown the nanomaterial used in the Venex textile is toxic to humans or animals.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that NDs could help the release of daunorubicin and overcome mechanisms of drug efflux, which induce resistance, therefore adding further evidence for the potential use of NDs to overcome MDR. In another study, Ghoneum et al ( 38 ) examined the effects of using a mixture of NDs and nanoplatinum (NP) known as DPV576 to overcome MDR in MDR human myeloid leukemic cells (HL60/AR) and MDR-sensitive cells (HL60). According to their results, the combination of daunorubicin with DPV576 was associated with higher incidence of the development of cell membrane holes in the MDR cells in comparison with the control cells that allowed better delivery of the drugs inside such cells.…”
Section: Nanotechnology Applications In Different Types Of Leukemimentioning
confidence: 99%